Exploring resident perceptions of initial competency based medical education implementation - Upadhyaya, Shivani; Rashid, Marghalara; Davila Cervantes, Andrea; Oswald, Anna (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Background: Competence by design (CBD) is a nationally developed hybrid competency based medical education (CBME) curricular model that focuses on residents’ abilities to promote successful practice and better meet societal needs. CBD is based on a commonly used framework of five core components of CBME: outcome competencies, sequenced progression, tailored learning experiences, competency-focused instruction and programmatic assessment. There is limited literature concerning residents’ perceptions of implementation of CBME.Objective: We explored resident perceptions of this transformation and their views as they relate to the intended framework.Methods: We recruited residents enrolled in current CBME implementation between August 2018 and January 2019. We interviewed residents representing eight disciplines from the initial two CBME implementation cohorts. Inductive thematic analysis was used to analyse the data through iterative consensus building until saturation.Results: We identified five themes: 1) Value of feedback for residents; 2) Resident strategies for successful Entrustable Professional Activity observation completion; 3) Residents experience challenges; 4) Resident concerns regarding CBME; and 5) Resident recommendations to improve existing challenges. We found that while there was clear alignment with residents’ perceptions of the programmatic assessment core CBME component, alignment was not as clear for other components.Conclusions: Residents perceived aspects of this transformation as helpful but overall had mixed perceptions and variable understanding of the intended underlying framework. Understanding and disseminating successes and challenges from the resident lens may assist programs at different stages of CBME implementation.